The use of technological innovations in military armaments -contemporary trends and future prospects - Małodobry , Zbigniew; Nastaj-Sałek, Karolina; Cyrkun, Katarzyna; Kuliński, Mariusz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
ASEJ ISSN: 2543-9103 ISSN: 2543-411X (online)-29-4Abstract—The aim of the work is to analyze the use of technological innovations in military armaments, with particular emphasis on contemporary trends and future prospects. In the context of dynamic technological development, the work aims to identify the main innovations in the field of armaments, their impact on changes in military tactics and strategy, and to predict the further development of these technologies. Research problems include questions about the role of new technologies, such as artificial intelligence, hypersonic weapons or autonomous weapon systems, in the future of military equipment and the challenges associated with their implementation. The research hypothesis assumes that technological innovations will have a key impact on revolutionizing the military -including changes in the structure of the army, operational effectiveness and international relations. Research methods include an analysis of the subject literature and case studies. The conclusions suggest that the development of new technologies will require appropriate international regulations, as well as new challenges related to ethics and security. Understanding these processes is crucial to ensuring global security.